2016
DOI: 10.1177/2056305116677137
|View full text |Cite
|
Sign up to set email alerts
|

Meaner on Mobile: Incivility and Impoliteness in Communicating Contentious Politics on Sociotechnical Networks

Abstract: This study explores the nature of how mobile social media may potentially be sharpening the tenor of communicating online. Specifically, randomized representative Twitter data were collected for several controversial issues, and then examined to determine the extent to which mobile or web-based content tends more toward greater incivility and impoliteness. Additional analyses further model how certain dialogic features, such as explicitly mentioning other users and retweeting others’ posts, positively relate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 48 publications
(53 reference statements)
0
39
1
Order By: Relevance
“…vote choice," and that the immediate effect was especially strong during the 2012 Senate debate. Additional research has suggested that different social media platforms may facilitate more uncivil behavior, particularly on mobile devices (Hmielowski, Hutchens, & Cicchirillo, 2014;Groshek & Cutino, 2016) and may reduce politeness (Halpern & Gibbs, 2013) or the willingness to open to others (Colleoni, Rozza, & Arvidsson, 2014).…”
Section: Active Passive and Uncivil Social Media Usementioning
confidence: 99%
“…vote choice," and that the immediate effect was especially strong during the 2012 Senate debate. Additional research has suggested that different social media platforms may facilitate more uncivil behavior, particularly on mobile devices (Hmielowski, Hutchens, & Cicchirillo, 2014;Groshek & Cutino, 2016) and may reduce politeness (Halpern & Gibbs, 2013) or the willingness to open to others (Colleoni, Rozza, & Arvidsson, 2014).…”
Section: Active Passive and Uncivil Social Media Usementioning
confidence: 99%
“…Each setting allows us to see a different perspective on identity" (p. 325). Groshek and Cutino (2016) extended Suler's original framework using hashtags of three controversial issues on Twitter to show that communication shared on the hashtags is often more uncivil and impolite than other forms of Internet communication. Moreover, in their roundtable conversation on hate speech online, Shepherd, Harvey, Jordan, Srauy, and Miltner (2015) discussed the hashtag infrastructure.…”
Section: Affordancesmentioning
confidence: 99%
“…The dissemination of information regarding progress in health-related fields such as genetics has grown considerably due to the ease of access to online information. However, the process of translation frequently involves simplifying or exaggerating information so as to capture attention [51, 52]. Without the requisite nuance in explanation and understanding, this information is easily misinterpreted.…”
Section: Introductionmentioning
confidence: 99%